1997
DOI: 10.1292/jvms.59.769
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal G1 Arrest in the Cell Lines from LEC Strain Rats after X-Irradiation.

Abstract: ABSTRACT. The effect of X-irradiation of cell lines from LEC and WKAH strain rats on a progression of cell cycle was investigated. When WKAH rat cells were exposed to 5 Gy of X-rays and their cell cycle distribution was determined by a flow cytometer, the proportion of Sphase cells decreased and that of G2/M-phase cells increased at 8 hr post-irradiation. At 18 and 24 hr post-irradiation, approximately 80% of the cells appeared in the G1 phase. On the contrary, the proportion of S-phase cells increased and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
2
13
2
Order By: Relevance
“…A linkage study of deficiency in repair of DSBs to the high sensitivity of radiation-induced apoptosis in LEC rat thymocytes is now in progress. We have also reported that LEC rat cells show an abnormality of transient cell cycle arrests that occur in normal rat cells following ionizing radiation [7,8,10]. Since it is well known that a regulatory pathway of cell cycle progression is associated with induction of apoptosis [12,23,32], abnormality of transient cell cycle arrests may be associated with the high sensitivity of radiation-induced apoptosis in LEC rat cells.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…A linkage study of deficiency in repair of DSBs to the high sensitivity of radiation-induced apoptosis in LEC rat thymocytes is now in progress. We have also reported that LEC rat cells show an abnormality of transient cell cycle arrests that occur in normal rat cells following ionizing radiation [7,8,10]. Since it is well known that a regulatory pathway of cell cycle progression is associated with induction of apoptosis [12,23,32], abnormality of transient cell cycle arrests may be associated with the high sensitivity of radiation-induced apoptosis in LEC rat cells.…”
Section: Discussionmentioning
confidence: 64%
“…In our previous studies using colony-forming assay to determine cell survival, we found that fibroblasts from LEC rats were more sensitive to X-irradiation than were cells from WKAH rats [9,17]. On the other hand, no significant difference was found in induction of apoptosis of LEC and WKAH rat fibroblasts by X-irradiation [10]. The present results showed that LEC rat thymocytes were more sensitive to induction of apoptosis by Xirradiation than were WKAH rat cells and that apoptosis was induced at an earlier incubation time after X-irradiation in LEC rat thymocytes than in WKAH rat thymocytes.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, LEC rat cells show abnormalities of transient cell cycle arrests from the G1 to S phase and at the G2/M phase after treatment of the cells with DNA-damaging agents [7,8]. Many studies suggest that abnormalities of cell-cycle checkpoint can contribute to the process of neoplastic transformation of the cells.…”
Section: Discussionmentioning
confidence: 99%